Whatsapp Addiction Affecting Students at Politeknik Sultan Mizan Zainal Abidin - Noor Rulhanim Binti Mohamad Ariffin; Norhafiza Binti Idris (Indonesian Institute for Counseling, Education and Therapy (IICET), 2018)
Nowadays, surfing the internet across virtual borders became a must to almost every layer of society. The existence of various social sites like Facebook, Twitter, Instagram and WhatsApp as medium to communicate became widely used because the internet is accessible to anyone regardless of place and time. Excessive use of WhatsApp is addictive and it gave different impact in terms of advantages and disadvantages to the users. Highlights from this, this paper work was done to assess the influence of the excessive use of WhatsApp on the attitude of students of PSMZA. A total of 250 students were randomly selected which consists of male and female students. The methodology used is descriptive method and quantitative approach that is using the questionnaire instrument consisting of three parts, namely part A respondent's demographic information, part B of the information level of addiction to the use of WhatsApp and part C information relating to the attitude of students either positive or negative towards their environment. The data collected is processed through the software IBM SPSS Statistics version 23. From the study it was found that the influence of the use of excessive WhatsApp still had positive impact on the attitudes of students of PSMZA. However, female students were more addicted to WhatsApp compared to male students.